2004
DOI: 10.3748/wjg.v10.i23.3433
|View full text |Cite
|
Sign up to set email alerts
|

Methylation profile of the promoter CpG islands of 14 “drug-resistance” genes in hepatocellular carcinoma

Abstract: Hypermethylation of promoter CpG islands of both CFTR and GSTpi genes occurs prevalently in HCC, which may correlate with the low expression of these two genes at the mRNA level and has the profound etiological and clinical implications. It is likely to be specific to the early phase of HCC carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 26 publications
0
60
1
1
Order By: Relevance
“…[5][6][7] Clinical studies investigating associations between carcinogenesis and abnormal methylation on CpG islands in tumor suppressor genes or genes involved in cell proliferation and death have been conducted in various cancers. [8][9][10][11][12] For HCC, it has been reported that some genes undergo hypermethylation in liver tissues, [13][14][15][16][17][18][19][20][21] supporting the hypothesis that determination of methylation in specific genes may be useful for HCC diagnosis. However, to the best of our knowledge, the diagnosis of HCC, in particular early HCC, based on the methylation levels of a single gene has not been clinically investigated to date.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…[5][6][7] Clinical studies investigating associations between carcinogenesis and abnormal methylation on CpG islands in tumor suppressor genes or genes involved in cell proliferation and death have been conducted in various cancers. [8][9][10][11][12] For HCC, it has been reported that some genes undergo hypermethylation in liver tissues, [13][14][15][16][17][18][19][20][21] supporting the hypothesis that determination of methylation in specific genes may be useful for HCC diagnosis. However, to the best of our knowledge, the diagnosis of HCC, in particular early HCC, based on the methylation levels of a single gene has not been clinically investigated to date.…”
mentioning
confidence: 89%
“…The development of the system was essential, as the results reported in previous studies by sequencing were insufficiently validated in clinical samples, and were limited to examination in a few patients and cell lines by non-quantitative sequencing analysis after cloning into plasmid vector DNA. [16][17][18][19][20]37 Moreover, in most reports the methylation status in HCC and non-HCC tissue samples has been evaluated by MSP assay without validation by sequencing, and is largely based on visual judgment of ambiguous PCR products amplified by nonquantitative MSP on agarose gels. 13,15,20,34 Therefore, the methylation status estimated by previous MSP assays may not represent the actual methylation profiles in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations